Fouling Monitoring and Control in Membrane Bioreactor - Trisno, Elmer Augustinus (2017)
Fouling is still a major issue in membrane filtration technologies that critically declines the filtration performance in the long term. There are many ways to control fouling, but their effectiveness depends on fouling characteristics. therefore, monitoring systems are developed and coupled with appropriate fouling control for a better fouling management. [1st Award]-[Peer Assessment Review]